The bullying-school shooting nexus: Bridging master narratives of mass violence with personal narratives of social exclusion. Issue 1 (2nd January 2019) - Raitanen, Jenni; Sandberg, Sveinung; Oksanen, Atte
ABSTRACT: This study examines the narratives that people who are deeply interested in school shootings tell about school shootings and their interest in the subject. Data come from 22 qualitative online interviews with individuals from 12 countries across the world, and the study is based on a framework of narrative criminology. We find that the theme of bullying weaves together personal narratives and the master narrative of school shootings. We discuss how deep interest in school shootings does not equal a desire to commit a massacre; rather, the circulation and recreation of the bullying story can reinforce scripts about responding to bullying with mass violence.